Azerbaijan : Health Sector Review Note, Volume 1, Main Report - World Bank (Washington, DC, 2012)
This two-volume Health Sector Review Note for Azerbaijan addresses the adequacy of the existing healthcare system to meet unmet healthcare needs and respond to epidemiologic and demographic challenges. The main rationale behind this Sector Note is to spur policymakers to consider a set of options for reforming the system, thereby enabling them to embark on a long-awaited reform initiative to improve health outcomes. The current system suffers from the following shortcomings: a legal and regulatory platform that is not conducive to effective system stewardship; fragmented accountability for technical, administrative and financial matters, excessive hospital and specialized care facilities; poorly funded and managed, as well as highly fragmented, primary healthcare services; a de-motivated health workforce that relies on informal payments to cope with low wages and a practice environment devoid of incentives; and, major inequalities in health and healthcare as a result of very low public outlays, coupled with increasingly high levels of out-of-pocket payments. The note makes a number of recommendations with a view to moving away from a model of specialist physician-centered care towards a model of family-based primary healthcare (PHC); a biomedical care model towards a model that values disease prevention and health promotion; a model that does not solve most health problems (referring them instead to higher levels) towards one where most problems are solved at the PHC level; a model with extremely inefficient resource allocation towards a model that allocates resources according to healthcare needs; and, a model where provider payments are based on inputs towards a model where providers are paid on the basis of productivity and the appropriateness and quality of the care they provide.